2020
DOI: 10.1136/bmjgh-2019-002093
|View full text |Cite
|
Sign up to set email alerts
|

Is development aid to strengthen health systems during protracted conflict a useful investment? The case of South Sudan, 2011–2015

Abstract: IntroductionIs achievement of Sustainable Development Goal (SDG) 16 (building peaceful societies) a precondition for achieving SDG 3 (health and well-being in all societies, including conflict-affected countries)? Do health system investments in conflict-affected countries waste resources or benefit the public’s health? To answer these questions, we examine the maternal, newborn, child and reproductive health (MNCRH) service provision during protracted conflicts and economic shocks in the Republic of South Sud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The country did not record significant gains during the millennium development goals era and is predicted to fall behind in the sustainable development goals era [36]. With a shrinking fiscal policy space and inadequate health spending, health governance and service models are compromised, often compounded by a fragmented health system that depends heavily on UN agencies, international NGOs, and other humanitarian aid organisations [37]. These challenges make it difficult to engage communities and government departments as co-designers and co-implementers and to embed CMSW programs fully into national health systems.…”
Section: Discussionmentioning
confidence: 99%
“…The country did not record significant gains during the millennium development goals era and is predicted to fall behind in the sustainable development goals era [36]. With a shrinking fiscal policy space and inadequate health spending, health governance and service models are compromised, often compounded by a fragmented health system that depends heavily on UN agencies, international NGOs, and other humanitarian aid organisations [37]. These challenges make it difficult to engage communities and government departments as co-designers and co-implementers and to embed CMSW programs fully into national health systems.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, one ecological study looked at the effectiveness of development financing for health in South Sudan, linking macro-level donor and government investment in health to outcomes at national level through a population survey. This study concluded that despite considerable domestic instability, donor funding to support HSS had resulted in statistically significant improvements in measles (11.2% improvement in coverage, +/- 4.2%, p<0.001), DTP3 (13.1 +/- 3.6, p<0.001) and all-vaccination coverage (11.3, +/- 3.0, p<0.001) over 5 years from 2011-2015, albeit from low levels (48). These global findings covered marked variation at sub-national level, for which the study could offer not mechanism-based explanation as data on information on service delivery models and partnerships at this level were not gathered.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies considered health financing interventions that ranged in focus from adaptive capacity building, to potentially transformative activities. These included two that looked at macro-level financing -specifically the value or otherwise of development aid in promoting improved health outcomes, including for vaccination, and system-strengthening in Gavi supported countries (47,48); one study that considered private sector provider engagement in routine immunisation provision (49); and four that considered in one way or another improvements to local level incentives for vaccination delivery (50)(51)(52)(53). Of these four, three studies considered explicit incentivisation to facilities or health workers via pay for performance (P4P) (50)(51)(52); and one considered improvements to disbursement of programme funds to local level to promote vaccination delivery as a means of reducing the risk of delayed payment to HCWs (53).…”
Section: Health Financingmentioning
confidence: 99%
“…South Sudan experiences a high volume of population movements and cross-border travel from both DRC and Uganda [8][9][10]. Nascent health and public health infrastructure, ongoing conflict, insecurity, population displacement and poor infrastructure limit the country's ability to rapidly respond and contain or limit an outbreak [11][12][13]. As South Sudan's health infrastructure works to recover from a protracted complex humanitarian emergency, the impact can be severe if an Ebola outbreak is not detected and contained early.…”
Section: Introductionmentioning
confidence: 99%